Хронологія та періодизація середньодніпровської культури Правобережної України - Бунятян, К.П. (Археологія, 2008)
Стаття є другою частиною розробки з хронології та періодизації середньодніпровської культури (див.: Археологія. — 2004. — № 1), присвяченої характеристиці скорчених поховань і поодиноких спалень. Вторая часть разработки по хронологии и периодизации среднеднепровской культуры (СДК) посвящена характеристике скорченных погребений и одиночных сожжений. Сопровождение данных погребений существенно отличается от вытянутых: кремневые и каменные изделия здесь встречаются чаще и нередко составляют единственное приданое умершего, посуда представлена классическими образцами. Это позволяет предположить в целом старший возраст, по крайней мере, части скорченных погребений. На основе стратиграфии кургана СДК (Подвысокое, к. 76) и с учетом типологических особенностей инвентаря гипотетично намечена трехчленная периодизация массива скорченных погребений. Первые две хронологические группы предшествуют вытянутым погребениям и синхронны c позднеямной культурой, третья — синхронна с вытянутыми и в общей периодизации культур эпохи бронзы совпадает с эпишнуровым горизонтом прикарпатского круга культур. Сопоставление радиокарбонных дат, полученных для территории Беларуси, а также погребений СДК на территории Малопольши, как и типологические особенности инвентаря датированных погребений, позволяет определить хронологию погребений в пределах примерно 27—20 вв. cаl BC. The second part of the work on the chronology and division into periods of Middle Dnipro Culture (MDC) is devoted to the description of crouched burials and individual cremations. Inventory of these burials signifi cantly differs from extended ones: fl int and stone wares are more frequently found here, and often form the only portion, while the vessels are of classic type. That allows the author to assume on the whole older age at least of part of crouched burials. Based on the stratifi ed mound of MDC (Pidvysotske, mound 76) and typological peculiarities of the inventory the trinomial division into periods of the bulk of crouched burials is hypothetically outlined. The fi rst two chronological groups precede the extended burials and are synchronous to the Late Yamna Culture; the third is synchronous to the extended burials and contemporizes with the Epi-Corded horizon of the circle of Subcarpathian cultures. Comparison of radiocarbon dates obtained for the territory of Belarus, and also of the MDC burials on the territory of Lesser Poland, as well as typological peculiarities of the inventory from the dated burials allow the author to determine the chronological limits of MDC within approximately the 27th—20th cc. cal. BC.